Infrastructure & Ops Superstream Series Building Security Into Your Development Lifecycle - Newman, Sam; McCune, Rory; Smith, Taylor; Look, Ping; Cochran, Chris; Ṭal, Liran; Salazar, Jed; Ivánkó, Natália (O'Reilly Media, Inc., 2021)
Sponsored by Aqua and Palo Alto Networks Security can't be added in at the end. We need to build it into everything we do ("pull left"). So how can developers get involved in building safer, more secure software? And what new skills do you need to learn to do so? About the Infrastructure & Ops Superstream Series: This five-part series of half-day online events details what you need to know to effectively manage existing legacy systems while migrating to modern, scalable, cost-effective infrastructures--with no interruption to your business. Each event day covers some of the most challenging and promising topics facing those working in infrastructure and operations today: continuous integration and delivery, cloud delivery, Kubernetes, microservices, and security. What you'll learn and how you can apply it Discover which tools work best for responding to threats Understand how to develop a cybersecurity strategy Learn how to recover from an attack on Kubernetes This recording of a live event is for you because ... You need to protect your systems from attacks by ransomware and emerging threats. You want to better understand the emerging threats landscape and what you can do to minimize and respond to attacks. You work with distributed systems and want to learn how to secure containers and Kubernetes. Recommended follow-up: Read " Security, Permissions, and Privacy " (chapter 9 in Learning Serverless) Read Kubernetes Security and Observability (early release book) Read Hacking Kubernetes (early release book) Read " Security and Backups " (chapter 11 in Cloud Native DevOps with Kubernetes) Read Building Microservices, second edition (book) Read Learning DevSecOps (early release book) Take Kubernetes Fundamentals in 3 Weeks (live online training course with Jon Johnson)